Tachycardia evoked from insular stroke in rats is dependent on glutamatergic neurotransmission in the dorsomedial hypothalamus. (9th July 2021) - Marins, Fernanda Ribeiro; Limborço‐Filho, Marcelo; Iddings, Jennifer A.; Xavier, Carlos Henrique; Biancardi, Vinicia C.; Stern, Javier E.; Ramiro Diaz, Juan; Oppenheimer, Stephen M.; Filosa, Jessica A.; Peliky Fontes, Marco Antônio
Abstract: Background and purpose: Damage to the insula results in cardiovascular complications. In rats, activation of N ‐methyl‐d ‐aspartate receptors (NMDARs) in the intermediate region of the posterior insular cortex (iIC) results in sympathoexcitation, tachycardia and arterial pressure increases. Similarly, focal experimental hemorrhage at the iIC results in a marked sympathetic‐mediated increase in baseline heart rate. The dorsomedial hypothalamic region (DMH) is critical for the integration of sympathetic‐mediated tachycardic responses. Here, whether responses evoked from the iIC are dependent on a synaptic relay in the DMH was evaluated. Methods: Wistar rats were prepared for injections into the iIC and DMH. Anatomical (tracing combined with immunofluorescence) and functional experiments (cardiovascular and sympathetic recordings) were performed. Results: The iIC sends dense projections to the DMH. Approximately 50% of iIC neurons projecting to the DMH express NMDARs, NR1 subunit. Blockade of glutamatergic receptors in the DMH abolishes the cardiovascular and autonomic responses evoked by the activation of NMDARs in the iIC (change in mean arterial pressure 7 ± 1 vs. 1 ± 1 mmHg after DMH blockade; change in heart rate 28 ± 3 vs. 0 ± 3 bpm after DMH blockade; change in renal sympathetic nerve activity 23% ± 1% vs. −1% ± 4% after DMH blockade). Experimental hemorrhage at the iIC resulted in a marked tachycardia (change 89 ± 14 bpm) that was attenuated by 65% ± 5% ( p  = 0.0009) after glutamatergic blockade at the DMH. Conclusions: The iIC‐induced tachycardia is largely dependent upon a glutamatergic relay in the DMH. Our study reveals the presence of an excitatory glutamatergic pathway from the iIC to the DMH that may be involved in the cardiovascular alterations observed after insular stroke. Abstract : Experimental hemorrhage at the insular cortex results in a marked sympathetic‐mediated increase in baseline heart rate. Here, it was found that bilateral blockade of glutamatergic receptors (with kynurenic acid) in the dorsomedial hypothalamus led to a 65% attenuation in the stroke‐induced increase in heart rate. Our study reveals the presence of an excitatory glutamatergic pathway from the insular cortex to the dorsomedial hypothalamus that may be involved in the cardiovascular alterations observed after insular stroke.